Native, alien, cosmopolitan, or cryptogenic? A framework for clarifying the origin status of rotifers - A Pociecha (Inter-Research, 2016)
Among small organisms, it is often difficult to distinguish native from alien species because we cannot easily determine where they originate. They are often labelled cosmopolitan or cryptogenic, euphemisms that indicate that we are uncertain of their origin. This lack of information obscures our understanding of biogeography and ecosystem functioning, thus limiting our ability to control biological invasions. Here, we propose a simple method using existing data to improve assessments of freshwater Rotifera. We tested the usefulness of 8 of 10 attributes of alien species, taken from a framework originally designed for distinguishing alien marine crustaceans, and added one new attribute. We used this framework to verify the origin status of 16 rotifers referred to in the literature as alien, cosmopolitan, tropicopolitan, or new to Europe. We assigned the alien status to 11 species that scored positively for at least half of the attributes; only 3 of these species were previously classified as alien in the literature. Cryptogenic status was assigned to 5 species, including 1 previously considered to be alien in Europe. The most efficient predictors of alien origin status were 2 attributes: appearance in areas where not previously found, and relatively restricted distribution in the assessed area compared to the distributions of native species. We propose this method as a first step towards assessing the status of a species whose origin is unclear, before more labour-intensive tools such as genetic analysis are employed. The use of a formal protocol to screen the existing data makes the origin status assessment transparent, open to discussion and subject to revision as new information becomes available.